Russia-European Union Borderlands: Transboundary Gradients, Interactions and Current Challenges - Kolosov, Vladimir A.; Klemeshev, Andrey P.; Zotova, Maria V.; Sebentsov, Alexander B. (International Journal of Economics and Financial Issues, 2015)
Research on post-Soviet borders emphasizes the need to combine traditional and relatively new approaches to border studies. For Russia, of special importance are the European Union (EU) borders accounting for almost half of the country’s international trade. The border districts of Russia and the neighboring EU countries have become natural drivers of regional integration processes. The post-Soviet history of the Russia-EU borderlands has shown dynamism and large dependence on the geopolitical situation, asynchronous changes in the border functions and regimes on different segments, dissimilar economic development rates, asymmetry in interactions between the parties, and a combination of debordering and rebordering processes. Over the past years, the deteriorating geopolitical situation and the economic crisis in Russia increased the risks of a stricter border regime and a significant reduction in border traffic. It is worth examining the correlation of stability and dynamism factors in the border situation. An important factor ensuring the persistence of current differences and problems is the inertia of the settlement system and territorial economic structure at all levels. These factors determine the fluctuations in demographic and socioeconomic indicators and thus contribute to the “difference of potential” ensuring border traffic. The authors analyze the impact of gaps in demographic and socioeconomic indicators on different segments of the Russia-EU border, as well as the asymmetry in transboundary interaction, on their stability in the period of increasing political tensions in 2014-2015. Special attention is paid to the effect of these interactions on the social development and everyday life in the Russian borderlands. It is stressed that, even in the conditions of a serious political crisis and reciprocal sanctions, the barrier functions of the Russia-EU border increased insignificantly. The driving force behind border interactions is pragmatism, which makes it possible for border districts to attract additional resources to solve local problems. Keywords: Border Districts, Russia, European Union, Transboundary Interactions, Asymmetry, Asynchrony, Border Regime, Border Cooperation JEL Classifications: F5, O5, R1